2013
DOI: 10.1002/pip.2387
|View full text |Cite
|
Sign up to set email alerts
|

A path towards a better characterisation of silicon thin‐film solar cells: depth profile analysis by pulsed radiofrequency glow discharge optical emission spectrometry

Abstract: The analytical potential of radiofrequency pulsed glow discharge optical emission spectrometry (rf-PGD-OES) is investigated for quantitative depth profiling analysis of thin-film solar cells (TFSC) based on hydrogenated amorphous silicon (a-Si:H). This method does not require sampling at ultra-high-vacuum conditions, and so it facilitates higher sample throughput than do reference techniques. In this paper, the determination of compositional depth profiles of a-Si:H TFSC was performed by resorting to a multi-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…A multi-matrix calibration procedure was adopted involving the use of CRMs without hydrogen and laboratory-prepared standards with hydrogen (doped layers of a-SiH). The GD-OES method 184 provided results in agreement with notional values for B-doped, intrinsic a-SiH, and P-doped layers (1.5%, 0.4% and 3.7% respectively). The OES technique was also able to provide layer thicknesses as low as 13 nm for the P-doped a-Si-H layer and it was suggested that it was possible to identify diffusion processes.…”
Section: Semiconductor Materials and Devicessupporting
confidence: 63%
See 1 more Smart Citation
“…A multi-matrix calibration procedure was adopted involving the use of CRMs without hydrogen and laboratory-prepared standards with hydrogen (doped layers of a-SiH). The GD-OES method 184 provided results in agreement with notional values for B-doped, intrinsic a-SiH, and P-doped layers (1.5%, 0.4% and 3.7% respectively). The OES technique was also able to provide layer thicknesses as low as 13 nm for the P-doped a-Si-H layer and it was suggested that it was possible to identify diffusion processes.…”
Section: Semiconductor Materials and Devicessupporting
confidence: 63%
“…The sensitivity and accuracy of the technique used to measure doping and trace elements is, therefore, critical. Thus, Sanz-Medel and co-workers investigated the quantitative depth proling of hydrogenated amorphous silicon (a-SiH) used in solar cells using a pulsed rf GD source with both OES 184 and MS 185 detection. A multi-matrix calibration procedure was adopted involving the use of CRMs without hydrogen and laboratory-prepared standards with hydrogen (doped layers of a-SiH).…”
Section: Semiconductor Materials and Devicesmentioning
confidence: 99%
“…Radio‐frequency glow discharge optical emission spectroscopy (rf‐GDOES) has been applied for diverse thin film analyzes, both on insulating and conducting layers. It has been used for example, for the analysis of PECVD SiO 2 layers, PVD Cu(In,Ga)Se 2 thin film and atomic layer deposition (ALD) ZnO . Most of the work has focused on the elemental concentration profiles and the development of the novel instrumental setups.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas depthwise elemental grading is known to be important for high efficiency CIGS solar cell [3], XRF can provide average composition only with a limitation in detecting light trace elements such as Na. Recently, glow discharge optical emission spectroscopy (GD-OES) was introduced as an alternative fast quantitative analysis method (a few tens of second) [4]. However, GD-OES measurement requires a relatively large sample size (a few cm 2 ) for vacuum holding, which is a disadvantage for repetitive measurement for product assessment due to increased loss of cell area.…”
Section: Introductionmentioning
confidence: 99%